2012
DOI: 10.1111/j.1540-8167.2012.02397.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute Versus Delayed Remote Ischemic Preconditioning on Reperfusion Induced Ventricular Arrhythmias

Abstract: Acute RIPC of the lower limbs induced a powerful delay in/and reduction in IR induced ventricular arrhythmias, but without evoking the RISK pathway; a late protective phase of RIPC on arrhythmias did not occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 42 publications
3
17
0
1
Order By: Relevance
“…Different authors have evaluated the possible intracellular mechanisms involved in the rIPC pathway. However, most of these studies have investigated mechanisms at time points that are different from the ones used in the present study [during early reperfusion or in late reperfusion (Dow et al 2012)] and also using different animal species (Konstantinov et al 2005;Donato et al 2013;Brandenburger et al 2014), making difficult to establish a comparison. In agreement with our findings, Li et al (2010) showed that rIPC induces activation of Phosphatidylinositol 3-kinase and inhibition of Glycogen synthase kinase before myocardial ischaemia.…”
Section: Discussionmentioning
confidence: 97%
“…Different authors have evaluated the possible intracellular mechanisms involved in the rIPC pathway. However, most of these studies have investigated mechanisms at time points that are different from the ones used in the present study [during early reperfusion or in late reperfusion (Dow et al 2012)] and also using different animal species (Konstantinov et al 2005;Donato et al 2013;Brandenburger et al 2014), making difficult to establish a comparison. In agreement with our findings, Li et al (2010) showed that rIPC induces activation of Phosphatidylinositol 3-kinase and inhibition of Glycogen synthase kinase before myocardial ischaemia.…”
Section: Discussionmentioning
confidence: 97%
“…; Dow et al . ), very little is known about the effect of RIPC on the incidence and severity of ischaemic tachyarrhythmias.…”
mentioning
confidence: 99%
“…In this regard, it seems worthwhile to perform additional experimental studies on RIPC, particularly those aimed at the investigation of RIPC protocols and end-points. For instance, while it is well established that RIPC results in infarct size limitation (Gho et al 1996;Birnbaum et al 1997;Pell et al 1998) and the attenuation of reperfusioninduced arrhythmias (Oxman et al 1997;Dow et al 2012), very little is known about the effect of RIPC on the incidence and severity of ischaemic tachyarrhythmias.…”
mentioning
confidence: 99%
“…Permite desde logo a redução da área de enfarte, do risco de arritmias de reperfusão 11,17 (nomeadamente extrassistolia, fibrilação e taquicardia ventricular 18 ) e preservação da função ventricular esquerda 19,20 .…”
Section: Mecanismos Fisiopatológicos Envolvidos No Pré-condicionamentunclassified